2022
DOI: 10.14202/vetworld.2022.124-131
|View full text |Cite
|
Sign up to set email alerts
|

Cervical anticancer activities of Annona squamosa Linn. leaf isolate

Abstract: Background and Aim: Cancer is one of the leading causes of death, the need for new anticancer herbal drugs is becoming more urgent considering the side effects of synthetic drugs. This study aimed to determine the anticancer activity of isolates derived from the methanol extract of Annona squamosa Linn. leaves and to identify the compounds that have an active effect against HeLa cells. Materials and Methods: The leaf metabolites of A. squamosa L. were extracted using methanol at room temperature (28°C) and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Studies have revealed anti-bacterial and anti-fungal properties [53] as well as anti-oxidant [54,55], anti-inflammatory [56,57], potential anti-diabetic [58], and neuromodulatory effects [59,60]. Many studies on plant extracts from other families containing loliolide have been carried out that proved a wide range of anti-cancer activities on different cell lines [61][62][63][64][65][66][67]. So far, loliolide has been isolated from other species of the Euphorbia genus, such as E. supina [68], E. micractina [69], E. cooperi [70], and E. alatavica [71] but has never been reported to be identified in E. turcomanica before.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed anti-bacterial and anti-fungal properties [53] as well as anti-oxidant [54,55], anti-inflammatory [56,57], potential anti-diabetic [58], and neuromodulatory effects [59,60]. Many studies on plant extracts from other families containing loliolide have been carried out that proved a wide range of anti-cancer activities on different cell lines [61][62][63][64][65][66][67]. So far, loliolide has been isolated from other species of the Euphorbia genus, such as E. supina [68], E. micractina [69], E. cooperi [70], and E. alatavica [71] but has never been reported to be identified in E. turcomanica before.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Annona plants are receiving special attention for their potent effects in combating cancer. Researchers are particularly interested in the remarkable anticancer properties exhibited by various compounds found within Annona species (72,73,98) . Moreover, there is a notable increase in studies concerning the applications of nanoparticle drug delivery systems in combination with different A. squamosa extracts for different therapeutic purposes (99)(100)(101) .…”
Section: 7wound Healing Activitymentioning
confidence: 99%
“…Toxicity test procedure followed Swantara et al (2022). Filtered seawater was used as a medium for hatching larvae.…”
Section: Toxicity Testmentioning
confidence: 99%